Her story set with CD-ROM - MacHaffie, Barbara J., 1949-; MacHaffie, Barbara J., 1949-; MacHaffie, Barbara J., 1949-; Fortress Press ([Minneapolis, Minn.] : Fortress Press, 2003)
Two works by MacHaffie are combined on this CD-ROM, with supplemental information and enhancements.
Title from disc label.
System requirements: Pentium 133MHz or better; 64MB RAM; Windows 98 or later; CD-ROM drive; 60MB free hard disk space.
Keywords: Women in Christianity -- History; Women in Christianity -- United States -- History